The seed-specific heat shock factorA9regulates the depth of dormancy inMedicago truncatulaseeds viaABAsignalling - Zinsmeister, Julia; Berriri, Souha; Basso, Denise Puntel [UNESP]; Ly-Vu, Benoit; Thi-Thu Dang; Lalanne, David; Amaral da Silva, Edvaldo Aparecido [UNESP]; Leprince, Olivier; Buitink, Julia (Wiley-Blackwell, 2020)
During the later stages of seed maturation, two key adaptive traits are acquired that contribute to seed lifespan and dispersal, longevity and dormancy. The seed-specific heat shock transcription factor A9 is an important hub gene in the transcriptional network of late seed maturation. Here, we demonstrate that HSFA9 plays a role in thermotolerance rather than in ex situ seed conservation. Storage ofhsfa9seeds ofMedicago truncatulaand Arabidopsis had comparable lifespan at moderate storage relative humidity (RH), whereas at high RH,hsfa9seeds lost their viability much faster than wild type seeds. Furthermore, we show that inM.truncatula, Mthsfa9seeds acquired more dormancy during late maturation than wild type. Transient expression of MtHSFA9in hairy roots and transcriptome analysis of Mthsfa9Tnt1 insertion mutants identified a deregulation of genes involved in ABA biosynthesis, catabolism and signalling. Consistent with these results,Mthsfa9seeds exhibited increased ABA levels and higher sensitivity to ABA. These data suggest that in legumes,HSFA9acts as a negative regulator of the depth of seed dormancy during seed development via the modulation of hormonal balance.
Keywords: ABA metabolism; ABA signalling; dormancy; longevity; thermotolerance